2007
DOI: 10.1016/j.uct.2007.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Combining vaccines with conventional therapies for cancer

Abstract: Preclinical and clinical investigations currently underway are employing novel strategies for combining vaccines with conventional and experimental anticancer therapies. To date, the FDA has not approved a therapeutic cancer vaccine. However, the results of recent investigations suggest an increasing role for vaccines in new models of combination therapy for many types of cancer. This article reviews and discusses therapeutic cancer strategies that employ vaccines in combination with local radiation, chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…This highlights the fact that tumor antigen must be expressed at high levels to elicit a robust and effective immune-mediated response. Additionally, mice that survived and received combination treatment with enzalutamide and Twist-vaccine for 12 months experienced antigen cascade (Supplemental Table 1), a host response not only to the antigen in the vaccine but also to other tumor antigens associated with a given tumor type (33, 4345). …”
Section: Discussionmentioning
confidence: 99%
“…This highlights the fact that tumor antigen must be expressed at high levels to elicit a robust and effective immune-mediated response. Additionally, mice that survived and received combination treatment with enzalutamide and Twist-vaccine for 12 months experienced antigen cascade (Supplemental Table 1), a host response not only to the antigen in the vaccine but also to other tumor antigens associated with a given tumor type (33, 4345). …”
Section: Discussionmentioning
confidence: 99%
“…In an effort to improve clinical outcomes, current therapies are being combined in order to treat cancer. Androgen ablation is a standard line of treatment for advanced prostate cancer and is being accessed in clinical trials in combination with immunotherapy (4042). Androgens have been found to transcriptionally regulate a variety of immune response genes (1315), therefore the effects of androgen ablation on the immune response is complicated and requires closer investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical models support the rationale for combining cancer vaccines with conventional therapies, such as radiation, chemotherapy, surgery, and hormone therapy. 23 Additionally, several studies have shown that patient cohorts who receive a cancer vaccine benefit clinically from subsequent therapies, compared with control cohorts. 24 Indeed, TroVax has been tested alongside 2 different standard of care chemotherapy regimens in patients with CRC.…”
Section: Discussionmentioning
confidence: 99%